2000
DOI: 10.1590/s0034-71082000000400007
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the ecology of proteocephalid cestodes, parasites of Sorubim lima (Pimelodidae), of the upper Paraná River, Brazil: II. Interspecific associations and distribution of gastrintestinal parasites

Abstract: One hundred and seven specimens of Sorubim lima (Bloch & Schneider, 1801) were collected in the floodplain of the upper Paraná River, Brazil between March 1992 and February 1996. Ninety-five specimens (88.78%) were parasited by at least a species of proteocephalid cestode. 7,573 parasites specimens of four different species were collected (average intensity 79

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…This fact was also verified by Pavanelli and Takemoto (2000) while analyzing gastrointestinal distribution of parasites in the intestines of Sorubim lima, the most abundant species of cestode was distributed along the entire organ, while other species showed preference for certain regions. Esch et al (1990) reported that the parasite community may be influenced by the age and length of the host, changes in the diet, in the volume of food ingested, ontogenetic changes in the immuno-competence and also, changes in probability of contact with intermediate hosts.…”
Section: Discussionmentioning
confidence: 57%
“…This fact was also verified by Pavanelli and Takemoto (2000) while analyzing gastrointestinal distribution of parasites in the intestines of Sorubim lima, the most abundant species of cestode was distributed along the entire organ, while other species showed preference for certain regions. Esch et al (1990) reported that the parasite community may be influenced by the age and length of the host, changes in the diet, in the volume of food ingested, ontogenetic changes in the immuno-competence and also, changes in probability of contact with intermediate hosts.…”
Section: Discussionmentioning
confidence: 57%
“…Fish assemblages suffer drastically due to the impact of reservoirs, which leads to predominance of generalist fish species (FREEMAN et al, 2001), depletion of migratory species (BRITTO; CARVALHO, 2006) and transference of pathogens and parasites (GABRIELLI;ORSI, 2000). Considering the impact of reservoirs on fish abundance, the prevalence and size of fish parasite infracommunities may also be influenced (PAVANELLI; TAKEMOTO, 2000). The Taquari River is the second biggest tributary of the Jurumirim reservoir (HENRY;NOGUEIRA, 1999) and is one of the main tributaries of the Paranapanema River, which has been significantly affected by the creation of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…However situations of high parasitological indexes from fish infected by Proteocephalidae, in Mexico (Pérez-Ponce de León et al, 1995), Paraguay (de Chambrier and Vaucher, 1994;1999), and Slovákia (Hanzelová et al, 2001) have also been described. In Brazil, this group of parasites has been studied in several fish species from the Paraná River (Rego and Pavanelli, 1987;Pavanelli and Santos, 1990;de Chambrier and Rego, 1995;de Chambrier et al, 1999;2006;Rego et al, 1998;1999;Pavanelli and Takemoto, 2000;Machado et al, 2000;Rego, 2002;de Chambrier, 2003) and from the States of Pará, Mato Grosso, Espírito Santo and Amazonas (Rego and Pavanelli, 1990;de Chambrier and Rego, 1994;Vaucher, 1997, de Chambrier, 2001;2003;de Chambrier et al, 2004ab;de Chambrier and Scholz, 2005).…”
Section: Introductionmentioning
confidence: 99%